2011
DOI: 10.2217/fon.11.99
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Histological Tumor Necrosis in Solid Organ Malignant Disease: A Systematic Review

Abstract: There is now a substantial body of evidence confirming the prognostic value of tumor necrosis in solid organ malignant disease. There are consistent associations between necrosis and the presence of other high-risk tumor characteristics but the survival impact appears to be independent of pathological stage. We propose that relationships with the host inflammatory response, both local and systemic, may explain the influence of tumor necrosis on cancer outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
104
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 62 publications
5
104
0
Order By: Relevance
“…Tumours contain areas of cellular necrosis, which is associated with poor survival in a variety of cancers2. Here, we show that necrosis releases an intracellular ion, potassium, into the extracellular fluid of mouse and human tumours causing profound suppression of T cell effector function.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Tumours contain areas of cellular necrosis, which is associated with poor survival in a variety of cancers2. Here, we show that necrosis releases an intracellular ion, potassium, into the extracellular fluid of mouse and human tumours causing profound suppression of T cell effector function.…”
mentioning
confidence: 73%
“…These factors cause dense areas of cellular apoptosis and necrosis 2. Tumour necrosis is frequently associated with a poor prognosis2, an observation thought to be an epiphenomenon of aggressive underlying cancer biology.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that necrosis in colorectal cancer (Richards et al 2012) and other tumors (Carlomagno et al 1995;Sengupta et al 2005) is associated with an upregulated systemic inflammatory response and decreased local inflammatory response (Richards et al 2011). Moreover, recent studies have confirmed that local inflammation was associated with higher survival , while systemic inflammatory response is regarded as a marker to predict poor outcome in colorectal cancer.…”
Section: The Role Of Tumor-associated Inflammationmentioning
confidence: 96%
“…Recent studies have shown that tumor necrosis (TN) influences metastasis-free survival in patients exhibiting neoplasms (1,2). In particular, TN has been reported to indicate poor prognosis in lung (3), breast (4,5), thyroid (6), colorectal (7,8), pancreatic (9) and renal (10–16) malignancies.…”
Section: Introductionmentioning
confidence: 99%